2012
DOI: 10.1002/pds.3264
|View full text |Cite
|
Sign up to set email alerts
|

An algorithm to identify preterm infants in administrative claims data

Abstract: Identification of prematurity based on gestational age ICD-9-CM codes is not sensitive. The prematurity score has superior construct validity and allows more comprehensive identification of preterm infants in the absence of birth certificates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Methods that assign a uniform duration of pregnancy [9][10][11][29][30][31][32][33][34] Easy to implement with limited data on mother and infant Estimated duration of pregnancy too long in preterm deliveries Yes 6,8,26,35 If preterm deliveries are excluded, distortion of distribution of pretermrelated exposures and events may occur Estimated duration of pregnancy too short in post-term deliveries 2. Methods that assign pregnancy duration based on preterm-delivery or related codes, or codes for other pregnancy outcomes 8,[12][13][14][15][16]34,[36][37][38] Exclusion of preterm births is avoided.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods that assign a uniform duration of pregnancy [9][10][11][29][30][31][32][33][34] Easy to implement with limited data on mother and infant Estimated duration of pregnancy too long in preterm deliveries Yes 6,8,26,35 If preterm deliveries are excluded, distortion of distribution of pretermrelated exposures and events may occur Estimated duration of pregnancy too short in post-term deliveries 2. Methods that assign pregnancy duration based on preterm-delivery or related codes, or codes for other pregnancy outcomes 8,[12][13][14][15][16]34,[36][37][38] Exclusion of preterm births is avoided.…”
Section: Methodsmentioning
confidence: 99%
“…Estimated duration of pregnancy too long in the earliest preterm deliveries Yes 8,15,16 Studies of exposures and outcomes related to preterm birth are feasible.…”
Section: Methodsmentioning
confidence: 99%
“…If these 2 dates were not available (about 13% of last menstrual period date is missing on birth certificates), this information was imputed from clinical estimate. [27][28][29] A previous study suggested that the last menstrual period from birth certificates and clinical estimates agreed within less than 2 weeks. 30 Continuous use of AEDs was defined as at least 2 consecutive prescriptions for AEDs or totaling more than a 30-day supply.…”
mentioning
confidence: 99%
“…For instance, we used gestational age from birth certificates considered as the criterion standard in a validation study of ICD-9-CM gestational age codes, which inadequately identified preterm infants. 24 Nevertheless, there are environmental risk factors for hospitalizations for RSV that could not be operationalized. One unmeasured and unadjusted risk factor, daycare attendance, deserves some discussion.…”
Section: Strengths and Limitationsmentioning
confidence: 99%